Stock Price Impact of Non-Performing Loans, Return on Assets and Earning per Share - Hertina, Dede; Bayu Herdiawan Hidayat, Mohamad; Deningtyas, Fika (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of non-performing loans, returns on assets, and earnings per share on stock prices in the banking sector listed on the Indonesia Stock Exchange in the period 2013-2017. The research methods used are descriptive and verification methods. The population of this study amounted to 43 banks, while the study sample used the purposive sampling technique of 31 banks. Data analysis using panel data regression analysis. The results of the study simultaneously showed that non-performing loans, returns on assets, and earnings per share affect the stock price. The research results partially show that Return On Assets have a positive effect on Stock Prices, while Non-Performing Loans and earnings Per Share are not significant on Stock Prices